Knowledge and Attitude with the Compliance of the use of Personal Protective Equipment (PPE) for Cleaning Officers - Farjiyanty Latif; Taswin Taswin; Fitriani Fitriani; La Ode Muh.Taufiq (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2023)
Introduction: According to the International Labor Organization, almost every year, there are 1000 times the number of non-fatal work accidents compared to fatal ones. To the income generated by workers. Purpose: This study determined the relationship between the level of knowledge and attitudes with the adherence to using personal protective equipment (PPE) for cleaners at the Environmental Office of Baubau City. Methods: This research is an analytic design with a cross-sectional study approach. The population and sample are all Baubau City Environmental Service cleaning workers, totalling 107 respondents using total sampling. Data collection techniques using a questionnaire, with chi-square data analysis. Results: research using the chi-square test shows that there is a relationship between knowledge (p-value = 0.000 <0.05) and Attitude (p-value = 0.000 <0.05) with Compliance with the use of personal protective equipment (PPE) for cleaning workers in Baubau City Environmental Service. Conclusion: there is knowledge about Compliance with using personal protective equipment (PPE) for cleaning staff at the Baubau City Environmental Service. There is a relationship between Attitude and Compliance with using personal protective equipment (PPE) for cleaning workers at the Baubau City Environmental Service.